A Systematic Review of Wave Speed and Wave Intensity Measures in the Human Carotid Arteries - Sandra Neumann; Kim H. Parker; Alun D. Hughes; Giovanni Biglino (Artery Research)
Abstract Wave intensity and wave speed are measures used to assess the dynamic properties of the arteries and travelling waves within the circulation. Wave intensity and wave speed measured in the carotid artery have the potential to provide hemodynamic and biophysical insights that can advance our understanding of the physiology of cerebral circulation. However, whilst studies have been performed in different patient cohorts exploring different methodological implementations of wave intensity analysis (WIA), to date little work has been done to unify wave measures or provide reference ranges on which to build the field of research and inform clinical practice. This review thus focuses on wave speed and wave intensity in the carotid artery in man with the aim to summarise the current knowledge of the field. From this review, the different methods of measurement and the disparity of the reported values currently hinder efforts to construct reference ranges for a comparator or intervention to be assessed.